Connection of images for making of technical document in CALS-technology - Форощук, І. В.; Ситник, О. Г. (Problems of Informatization and Control, 2009)
Intercommunication of effects of combination of images is considered for making of high-quality document in composition CALS-technology, which are presented as characteristic damages on the different areas of reproduction. Influence of combination on quality of images requires clarification of many theoretical moments. The got research job performances are directed on the decision of problem questions by the study of theoretical aspects of analysis of the phenomena which arise up at combination of images